Pengaruh Pengetahuan Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Pegawai Dinas Koperasi dan UKM Banten - Siti Nazihah Mahfudah; Ina Khodijah; Mochamad Fahru Komarudin (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2026)
Taxpayer compliance is a crucial factor in optimizing state revenue, particularly in supporting national development financing. However, in practice, various obstacles are still encountered that hinder the achievement of optimal compliance levels. Some of these include employees' low understanding of tax provisions and the less than optimal effectiveness of tax sanction implementation. This study aims to analyze the relationship between tax knowledge (X1) and tax sanctions (X2) on taxpayer compliance (Y) among employees of the Banten Province Cooperatives and SMEs Office. This study uses a quantitative method with an associative approach. The sampling technique uses saturated sampling, so that the entire population of 45 people is used as the research sample. Data analysis was performed using the Partial Least Square (SEM-PLS) based Structural Equation Modeling method using SmartPLS software version 4.0. The results show that the tax knowledge variable (X1) has a t-statistic value of 1.190 <1.96 and a significance value (p-value) of 0.234 >0.05. Thus, tax knowledge does not have a significant effect on taxpayer compliance. Furthermore, the tax sanction variable (X2) obtained a t-statistic value of 1.436 < 1.96 and a p-value of 0.151 > 0.05, which means that tax sanctions also do not have a significant effect on taxpayer compliance. Overall, this study concludes that neither tax knowledge nor tax sanctions partially have a significant effect on the level of taxpayer compliance among the employees who were respondents in the study. This finding indicates that other factors, such as personal awareness, perceptions of tax fairness, and intrinsic motivation, may have a more dominant role in shaping taxpayer compliance. Therefore, a more comprehensive policy strategy is needed to increase compliance, not only through increasing knowledge or enforcing sanctions, but also through ongoing coaching, socialization, and persuasive approaches.